Application Of Legal Procedures In The Examination Of The E-Court System - Kusbianto Kusbianto; Pratiwi Putri Marshanda Zaen (Legalpreneur Journal, 2023)
AbstractThe development of Information Technology has entered into all aspects of people's lives. Technology makes everything easier, not least with the world of court governance, it is alsorequired to be able to develop along with the development of society by utilizingtechnological sophistication in the form of an internet network, which can create a systemin forming an application called E-court. E-court is a form of change in the administrationof cases that are more transparent and accountability. The problems in this study are: howthe rules of legal procedure in the examination of the e-court system, how the effectivenessof the process of settlement of lawsuits in the e-court system in court. Based on the resultsof research and discussion, the e-court system in the process of settling lawsuits in courtcourts based on the principle of simple, fast and low cost has been running as its functionbut in practice the trial is still done manually. And there are still obstacles that are felt byadvocates / justice seekers that hinder the legal process to be less effective in itsimplementationKeywords: Examination, E-Court System, Procedures.